Phát triển nông sản hàng hóa ở Việt Nam trong giai đoạn hiện nay: Những vẫn đề đặt ra và giải pháp - Tuân, Nguyễn Mạnh (VNU Journal of Science: Legal Studies; Vol 20 No 3, 2004)
Our coutry’s agricultute made gigantic progress due to implemeting renovation policy for last many years. From the county, which was lack of food, at present we can not only supply enough food for consumption but also became the second largest rise export country in the world. People income and living standard have improved continuously. However, dispite of great achievement in the period of renovation, Vietnam agriculture and rural areas are facing many difficulties in the style of self - supply is still popular, development of goods production is not equal. Changing the economic structure of agricultural products in domestic and foreingn markets is low level in compare to many countries of the region and the world; Economic structure of argriculture of argriculture and rural areas are weak. Organization work, management and policy’s mechanism of argriculture development are still weak. Those problems given pressing tasks for Vietnam argriculture to be solved.